Diagnostic Delay in advanced Gastroesophageal Adenocarcinoma presenting as Chronic Neurogenic Dysphagia: Gastroesophageal Adenocarcinoma and Chronic Neurogenic Dysphagia - Abshori, Nuril Farid; Kakiay, Ferdinandus Stevanus; Ahdi, Iwal Reza; Patikawa, Febria Rizky (Clinical and Research Journal in Internal Medicine, 2026)
Advanced adenocarcinoma of the esophagogastric junction (AEGJ) may mimic benign or neurogenic swallowing disorders, leading to delayed diagnosis. We report a 65-year-old man with a two-year history of progressive dysphagia initially attributed to neurogenic causes following an ischemic stroke. The patient developed recurrent vomiting, epigastric pain, and significant weight loss (16 kg). On admission, he appeared cachectic (BMI 16.7 kg/m²) with anemia (Hb 7.7 g/dL) and hypoalbuminemia (2.4 g/dL). Contrast-enhanced CT revealed an infiltrative mass involving the distal esophagus and gastric fundus with lymphadenopathy, while endoscopy showed a friable obstructive lesion confirmed as adenocarcinoma on biopsy. A feeding jejunostomy was performed for nutritional optimization prior to oncologic therapy. The diagnostic delay resulted from anchoring bias, in which dysphagia was misinterpreted as neurogenic rather than structural. This case emphasizes the importance of early endoscopic evaluation in elderly patients with chronic progressive dysphagia, weight loss, or anemia, and highlights the need for clinician awareness of cognitive biases to prevent late-stage presentation and improve clinical outcomes.